Ethnoscience Project-based Learning Model on Colloid for Improving Students Critical Thinking - Habibati*, Habibati; Winarni, Sri; Suryani, Suryani; Hanum, Latifah; Ahmad, Nur Jahan (Jurnal IPA & Pembelajaran IPA, 2024)
The knowledge transfer of chemistry with unfamiliar topics may cause students to struggle to understand it. Conversely, if the concepts learned are associated with local wisdom through project assignments, it will produce meaningful learning. This study aims to analyze: the activities, learning outcomes, and students' and teachers responses to the ethnoscience-PjBL learning model. The research type is descriptive with a qualitative approach. The research subjects were 21 students of class XI-MIPA. Data collection techniques used were activity observation, tests, and students and teachers questionnaires. The research instruments included activity observation sheets, test sheets, and learners and teachers questionnaire sheets. The data was analyzed by using the percentage formula. The results showed that: (1) giving questions or problems step obtained an average percentage of 91.6%. The planning step, setting the work schedule, and monitoring the project gained an average percentage of 100%. The product assessment step obtained an average percentage of 82%. The project evaluation step obtained an average percentage of 62.5% in the application of the PjBL model, (2) the students learning outcomes reached an average score of 83.4, and (3) it received a positive response from students and teachers with an average percentage of 83.2% and 94% respectively. To conclude the application of the ethnoscience-laden PjBL model on colloid received positive responses and the completeness of learning outcomes reached a percentage of 100%